Detection of specific RBD+ IgG+ memory B cells by flow cytometry in healthcare workers and patients with inborn errors of immunity after BNT162b2 m RNA COVID-19 vaccination - del Pino Molina, Lucía; Bravo Gallego, Luz Yadira; Nozal, Pilar; Soto-Serrano, Yolanda; Martínez-Feito, Ana; Reche-Yebra, Keren; González-Torbay, Andrea; Cuesta-Martín de la Cámara, Ricardo; Gianelli, Carla; Cámara, Carmen; González-García, J.; González-Muñoz, Miguel; et al. (Frontiers in Immunology, 2023)
Inborn errors of immunity (IEI) are a heterogeneous group of diseases caused by intrinsic defects of the immune system. Estimating the immune competence of immunocompromised patients for an infection risk assessment or after SARS-CoV-2 vaccination constituted a challenge. The aim of this study was to determine the humoral responses of patients with IEI through a comprehensive analysis of specific receptor-binding domain-positive (RBD+) IgG+ memory B cells (MBCs) by flow cytometry, together with routine S-specific IgG antibodies and QuantiFERON SARS-CoV-2 (T-cell response), before the vaccine and 3 weeks after a second dose. We first analyzed the percentage of specific RBD+ IgG+ MBCs in healthy healthcare workers. Within the control group, there was an increase in the percentage of specific IgG+ RBD+ MBCs 21 days after the second dose, which was consistent with S-specific IgG antibodies. Thirty-one patients with IEI were included for the pre- and post-vaccination study; IgG+ RBD+ MBCs were not evaluated in 6 patients due to an absence of B cells in peripheral blood. We detected various patterns among the patients with IEI with circulating B cells (25, 81%): an adequate humoral response was observed in 12/25, consider by the detection of positive S-specific IgG antibodies and the presence of specific IgG+ RBD+ MBCs and S-specific IgG antibodies, presenting a positive T-cell response; in 4/25, very low S-specific IgG antibody counts correlated with undetectable events in the IgG+ RBD+ MBC compartment but with positive cellular response. Despite the presence of S-specific IgG antibodies, we were unable to detect a relevant percentage of IgG+ RBD+ MBCs in 5/25; however, all presented adequate positive T-cell response. Lastly, we observed a profound failure of B and T-cell response in 3 (10%) patients with IEI, with no assessment of S-specific IgG antibodies, IgG+ RBD+ MBCs, and negative cellular response. The identification of specific IgG+ RBD+ MBCs by flow cytometry provides information on different humoral immune response outcomes in patients with IEI and aids the assessment of immune competence status after SARS-CoV-2 mRNA vaccine (BNT162b2), together with S-specific IgG antibodies and T-cell responses.